Case Report: Portable handheld ultrasound facilitates intra-articular injections in articular foot pathologies - Ghandour, Samir; Taseh, Atta; Sussman, Walter; Guss, Daniel; Ashkani-Esfahani, Soheil; Gupta, Ashim; Waryasz, Gregory (Frontiers in Pain Research, 2024)
Background Intra-articular injections are commonly used to manage joint pathologies, including osteoarthritis. While conventional ultrasound (US) guidance has generally improved intra-articular injection accuracy, forefoot and midfoot joint interventions are still often performed without imaging guidance. This pilot study aims to evaluate the efficacy of office-based, portable ultrasound (P-US) guided intra-articular injections for forefoot and midfoot joint pain caused by various degenerative pathologies. Methods A retrospective analysis was conducted on a series of consecutive patients who underwent P-US guided intra-articular injections following a chief complaint of forefoot or midfoot joint pain. Patients reported their pain levels using the Visual Analog Scale (VAS) pre-injection and at 3 months follow-up. The procedure was performed by an experienced foot and ankle surgeon using a linear array transducer for guidance, and a 25-gauge needle was used to inject a combination of 2 cc 1% lidocaine and 12 cc of Kenalog (40 mg/ml). Complications and pain scores were analyzed using a paired t-test and p < 0.05 was considered significant. Results We included 16 patients, 31% male and 69% female with a mean age (±SD) of 61.31 (±12.04) years. None of the patients experienced immediate complications following the intervention. The mean pre-injection VAS score was significantly reduced from 5.21 (±2.04) to a mean of 0.50 (±1.32) at 3 months follow-up (P < 0.001). Thirteen patients reported complete resolution of pain at the 3-month follow-up. No adverse events were reported throughout the duration of the study. Conclusion This pilot study suggests P-US-guided intra-articular injections offer a safe and effective method for managing forefoot and midfoot joint pain caused by various arthritic pathologies. Further research is warranted to establish the long-term efficacy and comparative effectiveness of P-US-guided injections in larger patient cohorts as compared to non-image guided injections.